Safety in NATM tunnel construction: A systematic review of incidents, causes and prevention measures - Truong, Van Y; Nguyen, Tien Thuy; Nguyen, Tuan Anh; Nguyen, Trong Tam; Pham, Ngoc Thach; Nguyen, Tan Dong; Bui, Hong Dang (Journal of Transportation Science and Technology, 2026)
The New Austrian Tunnelling Method (NATM) is one of the most widely adopted techniques for tunnel construction in complex geological conditions, applied extensively in road, metro, and hydropower projects. NATM construction entails significant occupational hazards owing to confined working spaces, an unsupported excavation face, and intensive construction cycles. This paper presents a systematic review of NATM construction safety based on international incident databases, technical reports, and multidisciplinary peer-reviewed studies. Three principal findings emerge: collapses and daylight collapses account for 69% of all recorded incidents; unpredicted ground conditions — the most frequently cited external cause — typically reflect inadequate site investigation rather than truly unforeseeable geology; and management and supervision failures contribute to the majority of incidents. An integrated three-dimensional safety management framework — technical, organisational, and individual — combined with the Observational Method and modern monitoring technologies is proposed and discussed